Evolution of female‐specific wingless forms in bagworm moths. Issue 1 (21st November 2016) - Niitsu, Shuhei; Sugawara, Hirotaka; Hayashi, Fumio
SUMMARY: The evolution of winglessness in insects has been typically interpreted as a consequence of developmental and other adaptations to various environments that are secondarily derived from a winged morph. Several species of bagworm moths (Insecta: Lepidoptera, Psychidae) exhibit a case‐dwelling larval life style along with one of the most extreme cases of sexual dimorphism: wingless female adults. While the developmental process that led to these wingless females is well known, the origins and evolutionary transitions are not yet understood. To examine the evolutionary patterns of wing reduction in bagworm females, we reconstruct the molecular phylogeny of over 30 Asian species based on both mitochondrial (cytochrome c oxidase subunit I) and nuclear (28S rRNA) DNA sequences. Under a parsimonious assumption, the molecular phylogeny implies that: (i) the evolutionary wing reduction towards wingless females consisted of two steps: (Step I) from functional wings to vestigial wings (nonfunctional) and (Step II) from vestigial wings to the most specialized vermiform adults (lacking wings and legs); and (ii) vermiform morphs evolved independently at least twice. Based on the results of our study, we suggest that the evolutionary changes in the developmental system are essential for the establishment of different wingless forms in insects.